Respiratory virus behavior: Results of laboratory-based epidemiological surveillance - Hernández Bautista, Porfirio Felipe; Cabrera Gaytán, David Alejandro; Vallejos Parás, Alfonso; Moctezuma Paz, Alejandro; Santacruz Tinoco, Clara Esperanza; Alvarado Yaah, Julio Elias; Anguiano Hernández, Yu Mei; Martínez Miguel, Bernardo; Arriaga Nieto, Lumumba; Jaimes Betancourt, Leticia; Sandoval Gutiérrez, Nancy (PloS one, 2024)
Respiratory viruses have clinical and epidemiological importance. With the COVID-19 pandemic, interest has focused on SARS-CoV-2, but as a result, the number of samples available for the differential diagnosis of other respiratory viruses has increased. Cross-sectional study. To describe the epidemiological behavior of respiratory viruses based on a laboratory-based epidemiological surveillance system using data from 2017 to 2023. Univariate, bivariate and multivariate analyses of data from a laboratory database of respiratory viruses detected by multiplex RT‒qPCR were performed. A total of 4,632 samples with positive results for at least 1 respiratory virus, not including influenza or SARS-CoV-2, were analyzed. The most common virus detected was respiratory syncytial virus in 1,467 (26.3%) samples, followed by rhinovirus in 1,384 (24.8%) samples. Most of the samples were from children under 5 years of age. The age-adjusted odds ratio (OR) of death for patients infected with parainfluenza virus 4 was 4.1 (95% confidence interval [95% CI] 2.0-8.2). Respiratory syncytial virus and rhinovirus had the highest frequency and proportion of coinfections, whereas parainfluenza virus 4 was associated with an increased risk of death.